Ma’arif Literacy Movement Program in Improving Literacy Skills in Teachers and Students in Central Java - Ibda, Hamidulloh; Wijanarko, Andrian Gandi; Wijayanti, Dian Marta (Borneo International Journal of Islamic Studies (BIJIS), 2020)
The purpose of this study is to describe the Ma’arif Literacy Movement (GLM) program of the Educational Institution Ma’arif Nahdlatul Ulama of Central Java for the period 2018-2023. In addition, this study also revealed the character content, form and implementation of the Ma’arif Literacy Movement (GLM), the literacy of the teacher and the student abilities and obstacles in opportunities are the application of the Ma’arif Literacy Movement (GLM) program in Central Java. This research method is qualitative descriptive with interview, observation, and documentation techniques. As a result of the research, the Ma’arif Literacy Movement (GLM) program became the flagship program the Educational Institution Ma’arif Nahdlatul Ulama of Central Java which focuses on journalistic papers, scientific papers, literary works, technology works with independent practice and synergy practices. In this movement there is a character content from Strengthening Character Education (PPK) and the character of Aswaja Annahdliyah. The Ma’arif Literacy Movement (GLM) is a program that can improve the literacy skills of teachers and students in Central Java. That ability can be seen from the number of their works from the publication in the media of the Educational Institution Ma’arif Nahdlatul Ulama of Central Java totaling 1,139 works. While the number of products of journalistic papers, scientific papers, and literary works from the results of education and training / competitions until May 2020 is 364 works. There are four obstacles and seven opportunities to succeed the Ma’arif Literacy Movement (GLM) program in improving the literacy skills of Ma’arif’s teachers and students in Central Java.